SUBJECT AND PREVERBAL NOMINALS IN SASAK NGENO-NGENE PANCOR - Ahmady, Nur (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 16 (2009): March 2009, 2009)
Abstract This paper deals with the description and analysis of the preverbal nominals in basic intransitive and transitive clause in Sasak. Regarding to the variation found between syntactically accusative and ergative clauses in Sasak, this paper makes use of the LFG’s model of distinguishing the grammatical subject (subject for short) from the argument subject, the relation determined by semantic hierarchy at the D-structure (A-subject). This distinction allows us to explain the status of postverbal agent argument of objective voice (OV) in patient focus construction (PF). It is argued then that the preverbal arguments in OV and AV hold subject function. Its subjecthood is testified further by applying raising, equi NP deletion (PRO), and relativization. The tests prove that preverbal NPs constitute the subject and this makes us conclude that Sasak is syntactically ergative.